Can ESG Policy Become the Sustainability Catalyst of Company Performance During Covid-19 Pandemic? - Nora Sri Hendriyeni; Benediktus Tandya Pinasthika; Ilham Muhammad Akbar (Journal of Management and Business Review, 2023)
This study is conducted to discover the influence of environmental, social, and governance (ESG) policy on company performance during the Covid-19 pandemic. Both the company principal and agent are expected to consider the impact of developing a policy during the pandemic, especially concerning ESG policy. The ESG disclosure study aims to verify whether the policy, which is proxied with standard Global Reporting Initiative (GRI) disclosure in the sustainability report, influences company performance, which is proxied with Tobin’s Q ratio as a measure to discover the market response. It is founded on the urgency that the pandemic alters investors’ views about the company. This research failed to verify H1 or the influence of ESG disclosure on company performance. On the other hand, H2 and H3, including control variables, significantly influence company performance, as well as the Independence of the board of directors (BoD) and board of commissioners (BoC), which also have a significant but negative influence. This study has practical implications in which disclosure of ESG policy does not significantly influence company performance due to the management mindset, which still focuses on short-term conditions. It is thus necessary to develop a long-term strategic plan while taking sustainability into account.